DEVELOPMENT OF STEM EDP-BASED SCIENTIFIC ATTITUDE ASSESSMENT INSTRUMENT IN ELEMENTARY SCHOOL SCIENCE LEARNING - Nabila Alisyia Rahman; Din Azwar Uswatun; Astri Sutisnawati (Universitas Majalengka, 2025)
The purpose of this study was to determine the feasibility of the scientific attitude assessment instrument based on the STEM approach with the EDP model in elementary school science learning. This study uses the research and development method. The method used in this development research is based on the Borg & Gall development model. The trial subjects were grade V Al-Khawarizmi V Al-Jazari elementary school students. This study used instruments in the form of questionnaires and observation sheets. The overall validation results from experts reached a percentage of 80.5% with the category